Community-Based Management of Islamic Literacy Centers: Strengthening Non-Formal Religious Education - Ahmad Shadiq; Ismatul Izzah; Arifia Retna Yunita (Al-Qalam Institue, 2026)
This study aims to examine how community participation is integrated into the management of Qur'anic Learning Centers (TPQ) and to analyze its contribution to strengthening religious education among students. A qualitative research approach was employed, with data collected through observations, interviews, and document analysis. The participants included TPQ administrators, teachers, parents, and community members who were directly involved in educational activities. The findings reveal that TPQ management is primarily centered on routine educational programs, while planning and evaluation processes remain insufficiently systematic and sustainable. Community participation is reflected through voluntary services, financial support, and involvement in various activities. However, community engagement in program planning and decision-making processes is still limited. Despite these constraints, community support plays a significant role in maintaining the continuity of TPQ activities and fostering students’ religious values and practices. The study implies that a more structured and participatory management model is needed to enhance the effectiveness and sustainability of religious education. Strengthening collaboration between TPQ management and community stakeholders may contribute to improving educational quality and achieving long-term institutional development.